Kajian tabiat merokok di kalangan pelajar sekolah menengah daerah Pekan - Nor Kamisah Bte Abdul Hamid,; Niza Bte Samsuddin,; Asari Bin Abdullah,; Hashim Bin Md Safee’ie, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2001)
This research was done to study the factors that influenced the secondary school students to smoke in the District Of Pekan. The study was conducted from Jan-Feb 2000. The method of study was a stratified random sampling.From the study,the prevalence of smoking among the students was 40%.Means of the initiation age of smoking was 12.42 years. The prevalence among the male students was more compared to the female students i.e 60.5%. The prevalence of smoking at rural area was 45.29%.From the study ,we found that all students who smoke were also practising a negative habit likes drug abuse and glue sniffing.The prevalence of smoking among those who had friends who smokes also high i.e 73.81%.